Financial performance measures for Kansas swine farms, 1983-1992 - Michael R Langemeier; B M Purdy (Kansas Agricultural Experiment Station Research Reports, 1994)
Financial performance measures assist managers in making strategic plans and in tracking progress in relationship to a firm's goals. Kansas Farm Management Association data were used to compute benchmark financial performance measures for swine farms from 1983 to 1992. Annual average net farm income during the study period was $36,370 and ranged from a loss of $6,808 in 1983 to a profit of $69,418 in 1990. Return on investment ranged from -9.36% to 12.09% and averaged 3.71%over the period. The average debt to asset ratio was above 40% in every year except 1989, 1990, and 1992. The average debt to asset ratio was lower in 1992 (29 %) than in any other year of the study period.; Swine Day, Manhattan, KS, November 17, 1994
Keywords: Swine day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-175-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 717; Swine; Profitability; Liquidity; Solvency